Efecto del carbón activado y bioactivos en el control del hongo Phytophthora capsici en Ochroma pyramidale (Cav. ex Lam.) Urb. (balsa) - Mendoza Velez, Geraldine Maittee (2023)
demand in the international market. It is cultivated naturally and by reforestation, especially in the sub-tropical rainforest of Ecuador, where it is one of the forest and timber resources of superior use; being one of the most important economic items in our country, and called in international trade Ecuadorian balsam. Although it is a species of great commercial demand, it is not exempt from pathogen and disease attacks. The objective of this research was to determine the influence of activated charcoal and bioactives for the control of regressive death caused by the fungus Phytophthora capsici in Ochroma pyramidale (Cav. ex Lam.)